Match Running Performance of Elite Soccer Players and Correlations with Anthropometric and Power Indexes - Michailidis, Yiannis; Vardakis, Lazaros; Mikikis, Dimitrios; Mandroukas, Athanasios; Metaxas, Thomas (Journal of Sports Research, 2019)
The aim of this study was to investigate possible correlations between a) jumping ability (squat jump and countermovement jump performance) and c) anthropometric indexes with the distances covered at different intensities during soccer matches by Greek elite soccer players (n=11). Match running performance was analyzed using a global positioning system (GPS) within the second division professional league. Body weight and height were moderately correlated with the distance that was covered in the first half with the speed from 19.7 to 23.7 km/h (r=-0.605, p<0.05 and r=-0.616, p<0.05, respectively). No correlations were found between SJ and CMJ performance with match running performance in all the velocities. The players covered greater distances in the first half at all speed levels except for walking (6–11.9 km/h: 1,548 vs. 1,260 m, p<0.01; 12–15.7 km/h: 896 vs. 696 m, p<0.001; 15.8–19.6 km/h: 438 vs. 347 m, p<0.01; 19.7–23.7 km/h: 176 vs. 142 m, p<0.01; 23+ km/h: 71 vs. 52 m, p<0.001). The results demonstrated that match running performance depends on the tactical strategies of each team. Shorter players and who weight less may perform better in higher velocities. However, more studies with greater samples are needed to estimate the relations that were mentioned.